Proposing a Holistic Inclusive Education Model for Policy, Curriculum and Classroom Development - Christoph Teschers (New Zealand Journal of Teachers' Work)
The notions of inclusion and diversity have seen an increased used in a wide variety of areas in public debate and policy, and are widely used in educational documents in New Zealand and international since the UNESCO Salamanca Statement in 1994. What is meant by inclusion and diversity in many of these context is often rather unclear, however. The discourse of inclusion could be described as having become the standard for political correctness in official language, without always consequently reflecting on and applying the implications that the use of inclusive language implies. This includes educational settings such as schools and centres, but also government policies that use inclusive language and promote inclusion. It seems, however, that many centres and policies still operate under a mainstreaming/integration discourse mind-set. In educational philosophy and theory, the notion of inclusion and inclusive education has been discussed widely and many aspects relevant to inclusive practices have been discussed in depth. What seems in need of further attention are broader models and frameworks that capture the range of aspects involved and the complexity of inclusive education in theory and practice. One such model that focuses on five aspects of inclusive education will be introduced in this article and discussed how this model could support policy, curriculum and classroom decision making.